A predominantly neolithic origin for Y-chromosomal DNA variation in North Africa. - Arredi, B; Poloni, E; Paracchini, S; Zerjal, T; Fathallah, D; Makrelouf, M; Pascali, V; Novelletto, A; Tyler-Smith, C (2004)
We have typed 275 men from five populations in Algeria, Tunisia, and Egypt with a set of 119 binary markers and 15 microsatellites from the Y chromosome, and we have analyzed the results together with published data from Moroccan populations. North African Y-chromosomal diversity is geographically structured and fits the pattern expected under an isolation-by-distance model. Autocorrelation analyses reveal an east-west cline of genetic variation that extends into the Middle East and is compatible with a hypothesis of demic expansion. This expansion must have involved relatively small numbers of Y chromosomes to account for the reduction in gene diversity towards the West that accompanied the frequency increase of Y haplogroup E3b2, but gene flow must have been maintained to explain the observed pattern of isolation-by-distance. Since the estimates of the times to the most recent common ancestor (TMRCAs) of the most common haplogroups are quite recent, we suggest that the North African pattern of Y-chromosomal variation is largely of Neolithic origin. Thus, we propose that the Neolithic transition in this part of the world was accompanied by demic diffusion of Afro-Asiatic-speaking pastoralists from the Middle East.